JUVENILE DELINQUECY AND SUBSTANCE ABUSE; THE DYNAMIC DUO - Igbaekemen Goddy Osa (International Studies Journal)
This research article offers a critique to the issues raised by other scholars in the possession and use of alcohol and other drugs are illegal for all youth. Because substance abuse and delinquency are inextricably linked, arrest, adjudication, and intervention by the juvenile justice system are eventual consequences for many young people engaged in such behavior. Substance abuse and delinquency often share the common factors of school and family problems, negative peer groups, lack of neighborhood social controls, and a history of physical sexual abuse (Hawkins et al, 2007 Wilson and Howell, 2007). Substance abuse is also associated with violent and income-generating crime by youth, which increases community residents’ level of fear and the demand for juvenile and criminal justice services, thereby further increasing the burden on these resources. Gangs, drug trafficking, prostitution, and youth homicides are other related social and criminal justice problems often linked to adolescent substance abuse.